Repeat infections with chlamydia in women may be more transcriptionally active with lower responses from some immune genes - Huston, Wilhelmina M.; Lawrence, Amba; Wee, Bryan A.; Thomas, Mark; Timms, Peter; Vodstrcil, Lenka A.; McNulty, Anna; McIvor, Ruthy; Worthington, Karen; Donovan, Basil; Phillips, Samuel; Chen, Marcus Y.; et al. (Frontiers in Public Health, 2022)
Chlamydia trachomatis, the most common bacterial sexually transmitted infection worldwide, is responsible for considerable health burden due to its significant sequelae. There are growing concerns about chlamydial treatment and management due to widely documented increasing burden of repeat infections. In the current study, a cohort study design of 305 women with urogenital chlamydial infections demonstrated that 11.8% of women experienced repeat infections after treatment with azithromycin. The chlamydial DNA load measured by quantitative PCR was higher in women who experienced a repeat infection (p = 0.0097) and repeat infection was associated with sexual contact. There was no genomic or phenotypic evidence of azithromycin resistance within the chlamydial isolates. During repeat infection, or repeat positive tests during follow up, vaginal chlamydial gene expression (ompA, euo, omcB, htrA, trpAB) was markedly higher compared to baseline, and two of the selected immune genes analyzed had significantly lower expression at the time of repeat infection. Overall, there are two implications of these results. The results could be generalized to all recent infections, or repeat positive events, and indicate that chlamydial infections are have higher transcriptional activity of select genes early in the infection in women. Alternatively, after azithromycin treatment, repeat infections of Chlamydia may be more transcriptionally active at certain genes, and there may be post-treatment immunological alterations that interplay into repeat exposures establishing an active infection. The potential that recent infections may involve a higher level of activity from the organism may have implications for management by more regular testing of the most at risk women to reduce the risk of sequelae.